Anti-HIV-1 cycloartanes from leaves and twigs of Gardenia thailandica - Patoomratana Tuchinda (2018)
Thailandiol (1), gardenolic acid A (2), quadrangularic acid E (3) and 3β-hydroxy-5α-cycloart-24(31)-en-28-oic acid (4) have been isolated from the leaves and twigs of Gardenia thailandica Tirveng (order: Rubiales; family. Rubiaceae). In addition, 5-hydroxy-7,2′,3′, 4′5′6′-hexamethoxyflavone (5), 5,7-dihydroxy-2′, 3′, 4′,5′6′-pentamethoxyflavone (6), 5-hydroxy-7,2′,3′,4′,5′-pentamethoxyflavone (7) and 5,7-dihydroxy-2′,3′4′,5′-tetramethoxyflavone (8) were also isolated from the same source. The structures were elucidated by spectroscopic methods. Crude extracts and compounds 1-4 displayed anti-HIV-1 activities as determined by using theΔTat/RevMC99 virus and 1A2 cell line system. The EC50values determined by the syncytium assay ranged from < 7.8 to 110 μg/mL. They also exhibited moderate to high activities in reverse transcriptase (RT) assay; the IC50values of compounds 1-4, ranged from < 22.5 to 156.8 μg/mL.